The Conjoint/Disjoint Alternation in Bari and its Origins (The University of Nairobi Journal of Language and Linguistics, 2026)
This study describes the hitherto unknown morpho-syntactic alternation in Bari (Eastern Nilotic) that resembles what is called a “conjoint/disjoint” alternation in Bantu linguistics, and investigates its development. In Bari, this alternation has a peculiar attestation in dynamic transitive imperfective clauses, where the “conjoint” form is homophonous with the “focus” form of the verb, while the “disjoint” form is homophonous with the “potential” form. By analyzing various readings of these verb forms, as well as the other conjoint/disjoint-like alternations in various clause types (causative complement, relative, and sequential), we argue that the development of these alternations in Bari started with the functional expansion of the TAM-neutral “focus” form.
Keywords: Eastern Nilotic; Bari; conjoint/disjoint; focus; transitivity